A pedunculated small bowel gastrointestinal stromal tumour (GIST) masquerading as an ovarian tumour. Issue 12 (7th December 2021) - Turner, Lauren M; Jeans, Phillip; Robson, Stephen
Abstract: While gastro-intestinal stromal tumours (GIST) are the most common non-epithelial neoplasms of the gastrointestinal tract, 10% occur externally. Symptomatology is therefore broad, dependent on location. A 42-year-old female presented to the Emergency Department after 12 hours of severe right lower abdominal, preceded by vague pain over two weeks. Imaging revealed a right-sided 7.5 × 5.8 × 5.6 cm ovarian cystic lesion, suspicious for torsion. Laparoscopically, the lesion was densely adherent to small and large bowel, and she was proceeded to resection of an assumed primary ovarian neoplasm. Histopathology revealed an infarcted epithelioid GIST, high-grade with clear margins (stage pT3). There are only 24 cases of GISTs pre-operatively mistaken for gynaecological neoplasms. Additionally, there are reports of GISTs metastasizing to ovaries. Both computed tomography and ultrasound are non-specific, including hypo- and hyperechoic features. In all published cases, imaging was not able to identify presumed gynaecological neoplasms as GISTS. Differential diagnoses for pelvic masses should include non-gynaecological tumours.